2013
DOI: 10.1002/chem.201301846
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium‐Catalyzed Transfer‐Hydrogenative Cyclization of 1,6‐Diynes with Hantzsch 1,4‐Dihydropyridine as a H2 Surrogate

Abstract: The transfer-hydrogenative cyclization of 1,6-diynes with Hantzsch 1,4-dihydropyridine as a H2 surrogate was performed in the presence of a cationic ruthenium catalyst of the type [Cp'Ru(MeCN)3PF6]. Exocyclic 1,3-dienes or their 1,4-hydrogenation products, cycloalkenes, were selectively obtained, depending on the substrate structure and the reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…16 We have tested a series of Group 13 Lewis acids and organic donors towards alkene reduction, among which the cationic NHC gallium complex IPrGaCl 2 + and 1,4‐cyclohexadiene emerged as the best candidates 17. 18, 19 Furthermore, because gallium complexes efficiently catalyze the carbocyclization of arenynes into styrene derivatives,20 the procedure has been extended to a new type of transfer hydrogenative cyclization process akin to those using transition metals 21. 22…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 We have tested a series of Group 13 Lewis acids and organic donors towards alkene reduction, among which the cationic NHC gallium complex IPrGaCl 2 + and 1,4‐cyclohexadiene emerged as the best candidates 17. 18, 19 Furthermore, because gallium complexes efficiently catalyze the carbocyclization of arenynes into styrene derivatives,20 the procedure has been extended to a new type of transfer hydrogenative cyclization process akin to those using transition metals 21. 22…”
Section: Introductionmentioning
confidence: 99%
“…[17,18,19] Furthermore, because gallium complexes efficiently catalyze the carbocyclization of arenynes into styrene derivatives, [20] the procedure has been extended to a new type of transfer hydrogenative cyclization process akin to those using transition metals. [21,22] The triggering factor of this study was the surprising outcome of the gallium-assisted carbocyclization of arenyne 1 (Scheme 1). [20b] Instead of the expected product 3, ketone 2 was isolated in 76 % yield.…”
Section: Introductionmentioning
confidence: 99%
“…A cationic ruthenium catalyst of the type [Cp′Ru(MeCN) 3 PF 6 ] was used for the transfer‐hydrogenative cyclization reaction of 1,6‐diynes with Hantzsch 1,4‐dihydropyridine ester as H 2 surrogate for the synthesis of exocyclic 1,3‐dienes or their 1,4‐hydrogenation products and cycloalkenes (Scheme ) …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, when a 1,6-diyne possessing terminal methyl groups was used as the substrate, [2 + 2 + 2] cyclodimerization rather than transfer-hydrogenative cyclization occurred. Thus, we used cationic ruthenium complexes, [CpRu(AN) 3 ]PF 6 ( 1b , Cp = η 5 -C 5 H 5 , AN = MeCN) and [Cp*Ru(AN) 3 ]PF 6 ( 1c ), as the catalysts, which enabled the transfer-hydrogenative cyclization of various 1,6-diynes possessing terminal aryl, alkenyl, or alkyl groups using a Hantzsch ester (HE, 2 ) as an alternative H 2 surrogate (Scheme ) . However, 1,6-diynes possessing terminal alkyl groups were selectively converted into cycloalkenes via the 1,4-hydrogenation of the corresponding exocyclic 1,3-diene intermediates.…”
mentioning
confidence: 99%
“…We also demonstrated that the exocyclic 1,3-diene products efficiently underwent Diels–Alder reaction with highly electrophilic dienophiles such as N -phenylmaleimide, 4-phenyl-1,2,4-triazoline-3,5-dione, or dimethyl acetylene­dicar­boxylate . Recently, various tandem processes comprising catalytic 1,3-diene formations and subsequent Diels–Alder reactions have been developed for the rapid and diversity-oriented syntheses of complex polycyclic molecules. , Therefore, we also attempted the tandem ruthenium-catalyzed transfer-hydrogenative cyclization/Diels–Alder reaction of a 1,6-diyne in the presence of HE 2 and N -phenyl­malei­mide.…”
mentioning
confidence: 99%